2017
DOI: 10.1002/bjs.10588
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized and quasi-randomized clinical trials of topical antibiotics after primary closure for the prevention of surgical-site infection

Abstract: Topical antibiotics probably prevent SSI compared with no topical antibiotic or antiseptic. No conclusion can be drawn regarding whether they cause allergic contact dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The agents that could not be used systemically may also be used subcutaneously. There are also disadvantages such as tenderness and contact dermatitis [24].…”
Section: Discussionmentioning
confidence: 99%
“…The agents that could not be used systemically may also be used subcutaneously. There are also disadvantages such as tenderness and contact dermatitis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Topical antibiotics are also applied to the surgical wound to reduce SSI. Topical antibiotics can kill bacteria that cause SSI more effectively than systemic antibiotics because the concentration of antibiotics at the wound is higher than systemic antibiotics [17]. Although there is no su cient evidence that the application of topical antibiotics is bene cial, it is said to be bene cial in abdominal surgery in obese patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another strength was comparison of individual topical antibiotics to placebo or antiseptic, which was not done in similar studies. 6 , 8 …”
Section: Discussionmentioning
confidence: 99%
“… 7 On the other hand, through their systematic review and meta-analysis, Heal et al concluded topical antibiotics probably prevent SSIs compared to no antibiotic or with antiseptic. 8 …”
Section: Introductionmentioning
confidence: 99%